2003
DOI: 10.1097/00001888-200309000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Graduates??? Perceptions of Their Clinical Competencies in Allergy and Immunology

Abstract: The general competencies were considered important, but training in system-based practice and practice-based learning may be deficient. Although self-perceived competency in core areas of allergy and immunology was high, weaknesses in training and self-perceived competency in selected areas were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The challenges that face MFM educators and fellows are not unique to this subspecialty as many fields of medicine are ill-prepared to teach these topics to clinicians. 2,4 Previous studies have shown that systematic educational programs, including a web-based curriculum, can improve business practices among OBGYN residents 5,6 and similar programs would likely improve knowledge for MFM subspecialists. Currently, MFM fellows are exposed to web-based education through the Society for Maternal-Fetal Medicine Fellow Lecture Series on topics, such as clinical obstetrics, ultrasound, research, neonatology, and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges that face MFM educators and fellows are not unique to this subspecialty as many fields of medicine are ill-prepared to teach these topics to clinicians. 2,4 Previous studies have shown that systematic educational programs, including a web-based curriculum, can improve business practices among OBGYN residents 5,6 and similar programs would likely improve knowledge for MFM subspecialists. Currently, MFM fellows are exposed to web-based education through the Society for Maternal-Fetal Medicine Fellow Lecture Series on topics, such as clinical obstetrics, ultrasound, research, neonatology, and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…10 No existing instrument specific to plastic surgery, however, has been reported. Therefore, a new questionnaire was created as a screening survey across all competencies except medical knowledge.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…10,11 To keep the questionnaire length reasonable, the number of items was limited. There may have been insufficient domain representation to produce valid results for each competency.…”
Section: Plastic and Reconstructive Surgery • November 2009mentioning
confidence: 99%
“…Many residency program directors find that PBLI and SBP are difficult concepts to grasp [3], perhaps limiting their ability to develop effective means of teaching and evaluating these competencies [3,4]. It is likely that these challenges contribute to the perception of educators and learners alike that PBLI and SBP are the least important of the 6 general competencies endorsed by the ACGME [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%